Cost-Effectiveness Analysis of Capecitabine Plus Oxaliplatin Versus Gemcitabine Plus Oxaliplatin as First-Line Therapy for Advanced Biliary Tract Cancers - Chen, Ruijia; Zhang, Yalan; Lin, Kongying; Huang, Defu; You, MaoJin; Lai, Yanjin; Wang, Jinye; Hu, Yingying; Li, Na (Frontiers in Pharmacology, 2022)
Background: In the first-line treatment of BTCs, XELOX showed comparable clinical efficacy and safety to GEMOX, with fewer visits and better treatment management. Our study aims to investigate the cost-effectiveness of XELOX and GEMOX as the first-line therapy for BTCs from the perspective of the Chinese healthcare systems and to provide valuable suggestions for clinical decision-making. Methods: A Markov model was developed using the Phase 3 randomized clinical trial (ClinicalTrials.gov number, NCT01470443) to evaluate the cost-effectiveness of XELOX and GEMOX. Quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs) were used as the primary outcomes of the model. Uncertainty was assessed using univariate and probabilistic sensitivity analysis. Results: The QALYs for the XELOX and GEMOX groups were 0.66 and 0.54, respectively. In China, the total cost of XELOX treatment is 12,275.51, which is lower than the GEMOX regimen and more effective, making it the preferred regimen. Sensitivity analysis determined that XELOX therapy has a stable economic advantage in China. Conclusions: Compared to GEMOX, XELOX is a more cost-effective treatment as a first-line treatment for advanced BTC from the perspective of the Chinese health service system. Conclusions: XELOX, compared with GEMOX, is a more cost-effective treatment as the first-line treatment for advanced BTCs from the perspective of the United States and China’s health service system.